Perbedaan Efektivitas Ekstrak Daun Mangrove Acanthus ilicifolius Dengan Sodium Bikarbonat 5% Terhadap Penurunan Jumlah Koloni Candida albicans Pada Perendaman Nilon Termoplastik - Aviyuda Prabowo; Paulus Budi Teguh; Dwi Andriani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Nylon thermoplastic is denture base materials are often used. Dentures cleansing immersion can reduce calculus accumulation and Candida albicans (C.albicans) attachment. Sodium bicarbonate 5% is commonly used but has flaws. Acanthus ilicifolius leaves can be alternative herbal ingredients for denture cleanser because it has potency as antifungal and antibacterial. Purpose: To compare the difference in the effectiveness of antiC.albicans between Acanthus ilicifolius leaf extract and sodium bicarbonate 5% on nylon thermoplastic immersion. Materials and Methods: This study was true experimental laboratories with post test only control group design. The subjects in this study was a nylon thermoplastic soaked for 5 minutes and were divided into 5 groups: negative control group (DMSO 1%), positive control group (Sodium Bicarbonate 5%), and treatment groups (Acanthus ilicifolius leaf extract 1% , 0.5%, 0.25%). 0.1 ml of Sabouraud broth that has been contaminated with C.albicans in the immersion nylon thermoplastic then cultured in media SDA and incubated for 24 hours. Colony counted by colony counter in CFU/mL. The datawas processed by one way ANOVA and followed by LSD test. Result: There were differences in the number of colonies of C.albicans significantly between treatment groups with the negative control extract 1% and 0.5% (P <0,05) there is no significant difference between the negative control group with treatment group 3 (P3) (P>0,05). Conclusion: There were differences in the effectiveness of anti-C.albicans of Acanthus ilicifolius leaf extract concentration of 1% and 0,5% with sodium bicarbonate 5% on nylon thermoplasticimmersion